Study on the Pasture Establishment Technique Effect of Seed Rates, Methods of Sowing and Seed Treatments on Seedling Emergence in Cenchrus Ciliaris and Lasiurus Sindicus - Chakravarty, A K; Roy, R Deb; Verma, C M; Das, R B (Annals of Arid Zone, 2016)
.